2010
DOI: 10.1111/j.1365-2966.2010.17442.x
|View full text |Cite
|
Sign up to set email alerts
|

A torque formula for non-isothermal Type I planetary migration - II. Effects of diffusion

Abstract: We study the effects of diffusion on the non‐linear corotation torque, or horseshoe drag, in the two‐dimensional limit, focusing on low‐mass planets for which the width of the horseshoe region is much smaller than the scaleheight of the disc. In the absence of diffusion, the non‐linear corotation torque saturates, leaving only the Lindblad torque. Diffusion of heat and momentum can act to sustain the corotation torque. In the limit of very strong diffusion, the linear corotation torque is recovered. For the ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
896
1
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 504 publications
(955 citation statements)
references
References 33 publications
(74 reference statements)
30
896
1
10
Order By: Relevance
“…Since these first calculations, type I migration has been studied in great detail, and new formulations for type I migration rates are now available (Paardekooper et al 2010(Paardekooper et al , 2011. We use in our model an analytic description of type I migration that reproduces the results of Paardekooper et al (2011). A detailed description of this model is presented in Dittkrist et al (in prep.…”
Section: Orbital Evolution: Disc-planet Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since these first calculations, type I migration has been studied in great detail, and new formulations for type I migration rates are now available (Paardekooper et al 2010(Paardekooper et al , 2011. We use in our model an analytic description of type I migration that reproduces the results of Paardekooper et al (2011). A detailed description of this model is presented in Dittkrist et al (in prep.…”
Section: Orbital Evolution: Disc-planet Interactionmentioning
confidence: 99%
“…At ∼8 M ⊕ the protoplanet undergoes inward migration in the adiabatic saturated regime 5 (see Paardekooper et al 2010Paardekooper et al , 2011Mordasini et al 2010;Dittkrist et al). This timescale turns 5 The regime is called adiabatic when the local cooling timescale in the disc is longer than the time it takes for a parcel of gas to make a U-turn on the horseshoe orbit close to the planet in the corotation region.…”
Section: Planet Formation With Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this scenario, the solid core of the planet needs to form and initiate gas accretion at quite large radius from the star. This may occur if planetary cores can migrate outward because of the strong influence of corotation torques, as considered by [39] and [20]. Rapid gas accretion leading to a gap-opening planet is likely to require the formation of a massive core out at 15 au.…”
Section: Scenariomentioning
confidence: 99%
“…However, Rein (2012) has assumed that the smooth migration is always inward, which is only true for classic type I (and type II) migration. Recent improvements in the analysis of the corotation and horseshoe torques (plus the differential Linblad torque) have shown that type I migration can be outward in some regions of certain disk models, and that there are locations in the disk where the total torque vanishes and the migration is stalled (e.g., Paardekooper et al 2011;Kretke & Lin 2012). This more complex migration behavior means that it is possible for a pair of planets to undergo both convergent and divergent migration, as the disk accretion rate decreases with time and the disk depletes.…”
Section: Discussionmentioning
confidence: 99%